Motor Cortex Broadly Engages Excitatory and Inhibitory Neurons in Somatosensory Barrel Cortex. (31st March 2013) - Kinnischtzke, Amanda K.; Simons, Daniel J.; Fanselow, Erika E.
Abstract : Anatomical studies have shown that primary somatosensory (S1) and primary motor (M1) cortices are reciprocally connected. The M1 to S1 projection is thought to represent a modulatory signal that conveys motor-related information to S1. Here, we investigated M1 synaptic inputs to S1 by injecting an AAV virus containing channelrhodopsin-2 and a fluorescent tag into M1. Consistent with previous results, we found labeling of M1 axons within S1 that was most robust in the deep layers and in L1. Labeling was sparse in L4 and was concentrated in the interbarrel septa, largely avoiding barrel centers. In S1, we recorded in vitro from regular-spiking excitatory neurons and fast-spiking and somatostatin-expressing inhibitory interneurons. All 3 cell types had a high probability of receiving direct excitatory M1 input. Both excitatory and inhibitory cells within L4 were the least likely to receive such input from M1. Disynaptic inhibition was observed frequently, indicating that M1 recruits substantial inhibition within S1. Additionally, a subpopulation of L6 regular-spiking excitatory neurons received exceptionally strong M1 input. Overall, our results suggest that activation of M1 evokes within S1 a bombardment of excitatory and inhibitory synaptic activity that could contribute in a layer-specific manner to state-dependent changes in S1.